Features of transfusion therapy in hematopoietic stem cell transplantation - M. A. Kucher; D. E. Pevtcov; M. A. Estrina; N. E. Ivanova; O. A. Makarenko; B. A. Barishev; B. V. Afanasyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2016)
The aim of the research is to identify factors influencing the safety and efficacy of the transfusion therapy with hematopoietic stem cell transplantation (HSCT). From January 1 to December 31, 2015, 329 patients with hematologic diseases and malignancies who had undergone 367 HSCT were included into the study. Transfusion therapy was conducted in 345 HSCT – 94 % of cases. Totally, 9074 cases of transfusion of blood components were recorded: red blood cellcontaining – 2378 (26.2 %), plateletcontaining – 6255 (68.9 %), fresh frozen plasma – 441 (4.9 %). АВ0incompatibility between the donor and recipient was determined in 60.4 % of cases (n=154) in HSCT from allogeneic donor. Acute «graft versus host disease» was observed in 34.9 % of cases (n=89). Hemorrhagic complications were in 46 cases (12.5 %), mainly nasal, gastrointestinal bleeding and hemorrhagic cystitis. Pprevention and treatment of anemic and hemorrhagic complications in HSCT requires longterm and massive transfusion therapy with the availability of АВ0-incompatibility. The use of leukofiltrated, γ - or x-ray irradiated, individually and immunologically compatible blood components can reduce the risk of development of acute and delayed transfusion reactions in HSCT.